Effect of Physical Parameters on Modelling for Reduction of Propylene in Converters - Chauhan, Sanchita (Asian Journal of Chemistry, 2010)
Mathematical modelling for reduction in concentration of pollutant propylene in exhaust gas is carried out using catalytic converter. The performance of catalytic converters is highly dependent on its properties like cell density, catalytic surface area per unit reactor volume and length of the converter. The effect of varying these physical parameters on the conversion of propylene is analyzed.